Railway Service and Regulation - Ruggles, C. O. (Quarterly Journal of Economics, 1918)
War as emphasizing inadequacy of transportation facilities, 129. — Extra burdens upon transportation due to the war, 130. — History, extent and consequences of insufficient transportation facilities in the United States, 133. — Statistics of car shortage since 1907, 135. — Reasons for inadequate transportation facilities, 143. — Traffic conditions compared with expansion of railway plant, 143. — Duty of railroads to furnish adequate equipment, 145. — Popular misconception of car shortage, 146. — Aggregate supply of railroad equipment sufficient in most years, 149. — Relation of railroads to each other in exchange and interchange of cars; recent disregard of car service rules; unfortunate results of the historical relations of shipper and railroad, 150. — Early facilities in excess of needs, 153. — Significance of increase in number of commission and middle men, 157. — Position of Interstate Commerce Commission on reconsignment, 159. — Responsibility of government regulation, 161. — Importance of adequate return upon investment and transportation facilities, 161. — Necessity for extension of federal authority over railway service, 166. — Esch-Pomerene law only a beginning, 167. — Comprehensive control of railway service necessary even with continuation of government operation or adoption of government ownership, 170.